Internalization of Self-Confidence Characters in Junior High School Students in Banjarmasin City - Tarwilah, Tarwilah; Ahmad Rijali; Dahlan, Bayani (Journal of Research in Islamic Education, 2025)
Internalization of self-confidence character in Islamic Religious Education (PAI) learning as implemented by SMPN 6, SMPN 23, and SMP IT Nurul Fikri Banjarmasin is by using cooperative learning methods, namely lecture, question and answer methods, discussions, assignments, demonstrations, and sociodramas. All of these methods involve students actively, including in expressing opinions, asking questions and discussing in learning, so that good communication is established between students and students and students and teachers. Through this process, students' self-confidence character is formed, such as the growth of mutual respect, respect for the opinions of other friends, discipline, and students' self-confidence in conveying ideas and concepts, and being straightforward in conveying opinions when discussing or communicating the results of their work and ideas to teachers and friends. Internalization of students' self-confidence character in co-curricular and extracurricular activities at school also helps in forming students' self-confidence. Internalization of self-confidence character through co-curricular activities for students, namely giving students roles in flag ceremony activities, joint tadarus activities, AKSI which displays various student talents and skills, joint tadarus, the Qur'an recitation, reading of Maulid Habsyi and Commemoration of Islamic Holidays, public speaking, graphic design, gardening, and futsal.